Efektivitas Exercise Intradialisis Menggunakan Barbell dan Range of Motion (ROM) terhadap Adekuasi Hemodialisa pada Pasien Penyakit Ginjal Kronik - Yestiani Norita Joni; Busjra M Nur; Fitrian Rayasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to know the effectiveness of intradialysis exercise using barbells and Range of Motion (ROM) on the adequacy of hemodialysis in patients with chronic kidney disease in the hemodialysis room of RSIJ Sukapura in 2018. The design of this study uses a design with non-probability pre and post test two groups without control design . The result of the difference in the effectiveness of the adequacy values between the two intervention groups after the intervention was given was the barbell intervention obtained 1,33 with a standard deviation of 0.485, an error standard of 0.114. Whereas in the ROM intervention group 1.67 the standard deviation was 0.485, the standard error was 0.114 and the p-value was 0.047 (> 0.05). Conclusion, there was no significant difference in the value of hemodialysis adequacy between the barbellROM intervention groups after the intervention. Keywords: Hemodialysis Adequacy, Barbell, Exercise Effectiveness, Intradialysis, Range Of Motion (ROM)